Association between SRD5A2 rs523349 and rs9282858 Polymorphisms and Risk of Benign Prostatic Hyperplasia: A Meta-Analysis - Zeng, Xian-Tao; Su, Xin-Jun; Li, Sheng; Weng, Hong; Liu, Tong-Zu; Wang, Xing-Huan (Frontiers in Physiology, 2017)
ABSTRACT Objective: Previous studies have reported that rs523349 (V89L) and rs9282858 (A49T) polymorphisms in the gene 5α-reductase II (SRD5A2) are associated with the risk of benign prostatic hyperplasia (BPH), but different opinions have emerged. In view of distinct discrepancies among those findings, we performed this meta-analysis to ascertain a more accurate association between SRD5A2 rs523349 and rs9282858 polymorphisms and the risk of BPH. Methods: Studies investigating the association between SRD5A2 rs523349 and rs9282858 polymorphisms and susceptibility to BPH were searched from the databases of PubMed, Embase, Wanfang, and Chinese National Knowledge Infrastructure (CNKI). The strength of correlation was assessed by crude odds ratios (ORs) with their corresponding 95% confidence intervals (95% CIs). Moreover, subgroup analysis was conducted to further ascertain such relationship and investigate sources of heterogeneity. Results: SRD5A2 rs9282858 (A49T) polymorphism showed a significant correlation with increased BPH susceptibility under allele T vs. allele A genetic model (OR=2.51, 95% CI=1.29-4.88) in total analysis, and stratification analysis by ethnicity also revealed a similar association in Caucasian group under the same contrast. SRD5A2 rs523349 (V89L) polymorphism showed no significant role in BPH occurrence in total analysis, but its reducing and increasing effects on the disease risk were reflected in Caucasian and other-ethnicity subgroups, respectively, after stratification analysis by ethnicity. Conclusion: In conclusion, SRD5A2 rs9282858 polymorphism may elevate the susceptibility to BPH, while the polymorphism rs523349 may exert different influences on the disease in people of different ethnic lines.